ANALYSIS OF INCENTIVE FUND ALLOCATION IN IMPROVING THE WELFARE OF RELIGIOUS LEADERS - Islahudin (Universitas Muhammadiyah Metro), Ahmad Noor (Universitas Muhammadiyah Lampung, 2023)
Incentives are improvements given in the form of grants, can be in the form of rewards and so on, which aim to build the efficiency of representatives or the general public from organizations or public authorities. This proposition talks about the procedures for distributing motivator assets at strict figures where these assets are obtained from the Regional Revenue and Expenditure Budget and examines government assistance at strict figures that are in accordance with Islam. The fundamental issue in this study is the most common way of allocating driving assets for assertive figures in the Wates sub-region, Lampung Region and whether the motivation reserves that are deployed can work on government assistance to assertive pioneers in that sub-region in context of Islamic viewpoint. The examination strategy in this exploration is subjective with an interesting examination approach. Information sources in this examination consist of essential information sources and selected information sources. The information gathering strategy in this exploration is through perception, meetings and documentation. The author directed interviews to local governments, especially the Lampung Regional Individual Government Assistance Segment and the Wates Regional Social Assistance Segment. The examination methods used are information reduction, information display, and achievement determination. The essence of this research is to find out the top-down approach in dividing motivational assets for certain numbers and to see whether the reserves of encouragement channeled to certain numbers can develop further government assistance in accordance with the Islamic point of view. From the assessment that has been carried out, it appears that the most common way of distributing tight number motivator assets is still not in accordance with the Work Strategy Standards (SOP) for delivering tight number motivator assets in Regional Regulations. The circulation of motivational assets for strict figures cannot still be said to be ideal within the framework of this portion. Apart from that, from an Islamic perspective, the presence of propulsion subsidies distributed by the government has expanded government assistance to figures.